Depression and Anxiety Predict Healthcare Workers' Understanding of and Willingness to Help Suicide Attempt Patients. (June 2023) - Siau, Ching Sin; Chan, Caryn Mei Hsien; Wee, Lei Hum; Wahab, Suzaily; Visvalingam, Uma; Chen, Won Sun; Yeoh, Seen Heng; Tee, Jing Ni; Yeap, Lena Lay Ling; Ibrahim, Norhayati
We examined whether burnout, depression, anxiety, stress, lifetime suicidal ideation, self-efficacy in preventing suicide and demographic factors predicted the understanding of and willingness to help suicidal patients among hospital healthcare workers. A total of 368 healthcare workers from the major surgical and medical departments in a general hospital setting were recruited. Participants responded to the Depression Anxiety and Stress Scale-21, Self-efficacy in Suicide Prevention, and Understanding Suicide Attempt Patient Scale. Those from the psychiatric department, with higher suicide prevention self-efficacy, and lower personal accomplishment indicated more understanding and helpful attitudes; doctors, depressed and anxious healthcare workers reported less understanding and helpful attitudes. Suicide prevention efforts must be conducted in tandem with equipping and supporting the healthcare workers who manage suicidal patients.